Irregular Attendance of University Students at Class and its Relation to their Academic Achievement - Khanal, Shanti Prasad (Tribhuvan University Journal, 2019)
The paper intends to examine the irregular attendance of students in their class and its relation to their academic achievement in five central campuses of Mid- Western University. This study followed descriptive study based on quantitative and qualitative data. Quantitative data were obtained from 172 students selected by non-proportional stratified sampling. Qualitative data were obtained from the campus chiefs, heads of instruction committees and teachers of the central campuses selected purposively. A mixed questionnaire was employed for quantitative data and open ended questionnaire was used to collect qualitative data. The study showed that near about half portion of respondents responded that they were sometimes irregular in their class. Few students (4.45%) who were never irregular belonged to the category of having knowledge of irregular attendance. Higher portion (29.57%) of the male students were always irregular than the female students. The high portion of Master’s level students were always irregular than the Bachelor’s level students. Chhetri students were always irregular than other castes. The higher percentage (23.07%) of 20 to 25 years’ age group students were always irregular than other age groups. The percentage of irregular students seemed higher in central campus of Humanities and Social Science, Education and Management. Majority of the participants pointed out that the University related factors are main reasons for their irregular attendance. The study showed that there is a positive significant relationship between class attendance of students and their academic achievement.